Lack of Correlation between In Vitro and In Vivo Studies on the Inhibitory Effects of (‒)-Sophoranone on CYP2C9 Is Attributable to Low Oral Absorption and Extensive Plasma Protein Binding of (‒)-Sophoranone - Yu Fen Zheng; Soo Hyeon Bae; Zhouchi Huang; Soon Uk Chae; Seong Jun Jo; Hyung Joon Shim; Chae Bin Lee; Doyun Kim; Hunseung Yoo; Soo Kyung Bae (Pharmaceutics, 2020)
(‒)-Sophoranone (SPN) is a bioactive component of Sophora tonkinensis with various pharmacological activities. This study aims to evaluate its in vitro and in vivo inhibitory potential against the nine major CYP enzymes. Of the nine tested CYPs, it exerted the strongest inhibitory effect on CYP2C9-mediated tolbutamide 4-hydroxylation with the lowest IC50 (Ki) value of 0.966 ± 0.149 μM (0.503 ± 0.0383 μM), in a competitive manner. Additionally, it strongly inhibited other CYP2C9-catalyzed diclofenac 4′-hydroxylation and losartan oxidation activities. Upon 30 min pre-incubation of human liver microsomes with SPN in the presence of NADPH, no obvious shift in IC50 was observed, suggesting that SPN is not a time-dependent inactivator of the nine CYPs. However, oral co-administration of SPN had no significant effect on the pharmacokinetics of diclofenac and 4′-hydroxydiclofenac in rats. Overall, SPN is a potent inhibitor of CYP2C9 in vitro but not in vivo. The very low permeability of SPN in Caco-2 cells (Papp value of 0.115 × 10−6 cm/s), which suggests poor absorption in vivo, and its high degree of plasma protein binding (>99.9%) may lead to the lack of in vitro–in vivo correlation. These findings will be helpful for the safe and effective clinical use of SPN.